Responsibilities of staff development directors in nursing service as perceived by staff development directors in Illinois Hospitals evolution of role - Couper, Maria Christina Pilola Redona
The development of an effective nursing service to achieve quality patient care is a perpetual problem for hospital nursing administration. While the responsibilitiy for maintaining qualified staff falls on supervisors, the responsibility for developing their knowledge and skills falls primarily on the staff development director. According to Hutchinson, " before some aspect of behavior can play a part in the evolutionary process, it must become a standard feature of at least a large part of any population" ( 1974, 9. 168). Biddle and Thomas wrote that various aspects of real life behaviors may be examined, such as in the way the individual appraises hilself or others, the way people learn to perform, the way performances of some groups are related to those of other groups. Studies in role theory, according to them, sometimes focus on ...